Podatki z perspektywy katolickiej nauki społecznej - Zadroga, Adam (Annales. Etyka w Życiu Gospodarczym, 2013)
Taxes are closely related to the functioning of the state. From the moral and social point of view, it should always be directed towards the common good. Implementing this principle, the state supports the improvement of citizens’ welfare. Provides them with collected taxes their services, such as internal and external security, education, culture, infrastructure, social services and others. The formation of fair tax system and the mechanism of budgetary resources also has great importance because of the importance of the whole economy. In addition, the state’s fiscal system applies to every citizen as a taxpayer. Therefore, this issue also has important ethical dimension of individuality. The article focuses on these issues, emphasizing an ethical perspective the following three issues: (1) The social context of contemporary reflections on the obligations to the state, (2) the state and its goals, and (3) the moral aspects of the duty to pay taxes.